Transfer Pricing in China - Devonshire-Ellis, Chris; Scott, Andy.; Woollard, Sam.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This Guide is a detailed overview of all aspects of transfer pricing in China. Produced in association with Transfer Pricing Associates, a specialist global transfer pricing firm, this is an essential work for any businessman trading with or conducting business in China. The book deals with all aspects of transfer pricing from a practical perspective, from designing and implementing a transfer pricing system, to managing China compliance and preparing for an audit.
Designing and Implementing a Transfer Pricing System -- Identifying the Relevant Business Context -- Transfer Pricing Disclosures and Documentation -- Tax Return Disclosures -- Managing China Compliance -- Preparing Documentation -- Transfer Pricing Risk Management -- Transfer Pricing Audits and Enforcement -- Income Adjustments -- Penalties and Interest -- Managing an Audit -- Advance Pricing Arrangements -- Cost Sharing Agreements -- Thin Capitalization.
Electronic reproduction.
Keywords: Transfer pricing -- China; Electronic books